The Age of Establishment of the Company after the Enactment of the Job Creation Law - Yalid Yalid; Irawan Harahap; Riantika P ratiwi (Syntax Idea)
This study examines the conflict of age proficiency norms related to the establishment of the company since the post-enactment of the job creation law. As is known, the establishment of an individual company according to Article 6 paragraph (2) letter A of Government Regulation Number 8 of 2021 can be carried out by Indonesian citizens who are 17 years old and legally competent. The age of establishment of the individual company is clearly not in sync with the age of proficiency norms in the Civil Code. The problem will occur if later the individual company is converted into a Limited Liability Company while the age of its founder has not reached 21 years, while converting an individual company into a Limited Liability Company must be done through an agreement. The research method is carried out in a normative manner, with the approach of legislation, Court decisions, legal concepts and comparisons, using legal materials and analyzed and interpreted comprehensively. The results of this study proficiency in establishing the company the author chose the ideal concept only option. Some countries use the 18-year-old adult age benchmark in some laws using the 18-year-old size and some experts agree that the 18-year-old adult size is thus the size of an 18-year-old adult is an appropriate size for the skills of people related to establishing a company